General Practice Nurses' experiences of changing care delivery during COVID‐19. Implications for future practice: Qualitative study protocol. (27th May 2022) - Anderson, Helen; Scantlebury, Arabella; Galdas, Paul; Adamson, Joy
Abstract: Aim: To explore how General Practice Nurses experience implementing change at pace and scale in delivering care during consecutive waves of the COVID‐19 pandemic. To evaluate the impact of changes to general practice nurses' working practices on professional wellbeing. Background: In response to the COVID‐19 pandemic, general practice rapidly and extensively changed care delivery. There has been little exploration of the experiences of General Practice Nurses and care delivery, job satisfaction, workload, stress and professional support. Design: A qualitative case study design of three to five general practice case sites will explore General Practice Nurses' experiences during the Covid‐19 pandemic. The study was funded and approved by the General Nursing Council Trust in June 2021. University ethics approval was gained in July 2021. Health Research Authority approval has been obtained [IRAS:30353. Protocol number: R23982. Ref 21/HRA/5132. CPMS: 51834]. Methods: Data will consist of focus groups and/or semi‐structured interviews with General Practice Nurses, primary healthcare team members and other key informants. Business/strategy and nurse team meetings relating to workforce planning/review will be observed. Documents will be analysed and routinely collected general practice data will provide descriptive contextualisation at each site. The study will be theoretically underpinned by the Non‐adoption, Abandonment, Scale‐up, Spread and Sustainability Framework and data analysed using framework analysis. Discussion: General Practice Nurses have a unique sphere of knowledge and undertake specific work in primary care. This workforce is challenged by recruitment, retention and retirement issues, leading to the loss of highly experienced and knowledgeable professionals. It is important to explore how working practices brought about by Covid‐19 affect General Practice Nurses. Impact: This study will explore working practices brought about by the Covid‐19 pandemic to inform care delivery, patient care and support General Practice Nursing workforce wellbeing and will highlight and mitigate negative aspects of novel and changing care delivery. Key factors in implementing and supporting future practice and change implementation will be developed. Trial registration: CPMS: 51834.